2021
DOI: 10.3389/feduc.2021.678793
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Special Educators’ Understandings of Relational Competence

Abstract: Research demonstrates that the teacher-student relationship is essential for students with special educational needs. This article investigates how pre-service special educators (n = 74) perceive teachers’ relational competence, as manifested in their relations with students exhibiting behavioral difficulties. The data comprises educators’ written analyses of teacher-student interactions simulated through digital video, both before and after being provided with explicit criteria on teachers’ relational compete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
0
12
0
7
Order By: Relevance
“…Keterhubungan sosial sangat erat hubungannya dengan keterlibatan secara akademik dan non-akademik (Ng & Chu, 2021). Hubungan guru dan siswa menjadi sangat penting untuk diperhatikan agar dapat mengembangkan pembelajaran bermakna (Zydziunaite et al, 2021) sehingga berdampak positif pada aktivitas sosial (Aspelin et al, 2021), afektif dan akademik siswa (Ayuwanti et al, 2021). Siswa menjadi lebih matang dalam bersosialisasi bila dibekali dengan interaksi secara sehat bersama guru.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Keterhubungan sosial sangat erat hubungannya dengan keterlibatan secara akademik dan non-akademik (Ng & Chu, 2021). Hubungan guru dan siswa menjadi sangat penting untuk diperhatikan agar dapat mengembangkan pembelajaran bermakna (Zydziunaite et al, 2021) sehingga berdampak positif pada aktivitas sosial (Aspelin et al, 2021), afektif dan akademik siswa (Ayuwanti et al, 2021). Siswa menjadi lebih matang dalam bersosialisasi bila dibekali dengan interaksi secara sehat bersama guru.…”
Section: Pendahuluanunclassified
“…Pada level pendidikan sekolah dasar, Coşkun & Kara (2020b) melakukan investigasi terkait strategi penyesuaian sikap siswa tahun pertama di sekolah dasar, namun tidak ada keterangan yang fokus pada sekolah dasar pedesaan. Aspelin et al (2021) melaksanakan riset yang melibatkan guru dari anak berkebutuhan khusus dan guru mengalami pergeseran persepsi dari awalnya yang lebih fokus pada strategi pengajaran menuju hubungan yang terbuka antara siswa dan guru. Jenjang selanjutnya, Liu & Gillies (2021) menyimpulkan bahwa interaksi guru dan siswa SMA di Cina dalam pembelajaran bahasa, dapat dimediasi melalui pertanyaan-pertanyaan yang diberikan guru yang berbentuk pertanyaan referensial (jawaban diperoleh dengan cara menalar, menganalisa, mengevaluasi, dan menformulasikan ide).…”
Section: Pendahuluanunclassified
“…An important effort toward the inclusion of relational competencies in teacher training has been initiated, both in policy and research, in Denmark and Sweden (Jensen et al, 2015;Aspelin and Jonsson, 2019). In various, in-depth qualitative studies, researchers have investigated how (pre-service) teachers themselves conceptualize "relational competence, " how relational competencies are visible in teachers' practice, and how teacher education can strengthen teachers' relational competencies (Jensen et al, 2015;Aspelin and Jonsson, 2019;Aspelin et al, 2020Aspelin et al, , 2021. This line of research conceptualizes relational competence as "being able to meet students and parents with openness and respect, to show empathy and to be able to take responsibility for one's own part of the relationship as an educator" (Jensen et al, 2015, p. 206).…”
Section: Teachers' Relationship-building Competencementioning
confidence: 99%
“…Research indicates that beginning teachers and teachers working with children with special educational needs are particularly prone to negative emotions and are more likely to experience conflict in their teacher-child relationships (Kelchtermans and Deketelaere, 2016;Zee et al, 2020;Zendarski et al, 2020;Roorda et al, 2021). Scholars have suggested that teachers are often not sufficiently prepared for the emotional and relational aspects of working with (special needs) children (Stempien and Loeb, 2002;Brunsting et al, 2014;Jo, 2014;Aspelin and Jonsson, 2019;Aspelin et al, 2021). To date, teacher education programs primarily focus on formal (subject) knowledge and teaching skills, and pay far less attention to relational and emotional competencies that are necessary for building positive relationships with children (Jensen et al, 2015;Aspelin and Jonsson, 2019).…”
Section: The Teacher-child Relationship and Teacher Emotionsmentioning
confidence: 99%